A Point-Light Display Model for Teaching Motor Skills to Children With Autism Spectrum Disorder: An Eye-Tracking Study. Issue 4 (August 2021) - Saber Sotoodeh, Mohammad; Taheri-Torbati, Hamidreza
People with autism spectrum disorder (ASD) have limitations in their attention and working memory that affect their motor learning. The aim of current study was to compare point-light display (PLD) to video observation as instructional models for teaching motor skills to children with ASD versus typically developing (TD) children. We randomly assigned 24 children with ASD aged 6-17-years-old and 24 age paired typically developing (TD) children to four groups: (a) ASD-Video, (b) ASD-PLD, (c) TD-Video, and (d) TD-PLD. After twenty training blocks (200 trials), all participants entered into late retention and transfer testing. We recorded all participants' visual gazes when observing each PLD and Video condition. Both PLD groups had better performance in the acquisition phase, and on retention and transfer tests. Also, gaze recordings revealed that children with ASD paid more attention to relevant demonstration points in the PLD than in the video condition. We discuss possible mechanisms and implications of these findings.